Osuuskauppa Keskimaan asiakasomistajien käsityksiä vastuullisesta liiketoiminnasta - Ruusuvirta, Leena (2012)
This Master’s thesis considers corporate responsibility of co-op company Keskimaa and especially, how customer owners of Keskimaa understand two similar definitions: corporate responsibility and sustainable development. Literature part describes characteristics of corporate responsibility, ethical and moral basis and values. The value basis of co-op Keskimaa is briefly introduced and three bottom lines of corporate responsibility are discussed. The theoretical framework of the study is consisted of stakeholder theory and especial role of customer-owners is evaluated. Empirical part of the study contains 84 interviews of customer owners of Keskimaa done during the winter 2012 mainly in co-op Keskimaa’s supermarkets. Interviews were based on structured questions. This study combines quantitative and qualitative research and as a result, it seems that corporate responsibility is more common term among customer owners than sustainable development. To improve corporate responsibility of co-op Keskimaa customer-owners emphasized that Keskimaa should pay attention to social responsibility of the business and increase collaboration with local producers and suppliers.